2019
DOI: 10.1002/jrs.5629
|View full text |Cite
|
Sign up to set email alerts
|

Raman mapping of 4‐MeV C and Si channeling implantation of 6H‐SiC

Abstract: A 6H‐SiC single crystal implanted in channeling mode by 4‐MeV C+3 and Si+3 ions at various doping levels has been examined by scanning electron microscopy (SEM) and micro‐Raman spectroscopy in order to study the lattice distortions inflicted by the impinging ions. C ions create zones of strongly damaged regions, parallel to the front face of the wafer with width increasing with the amount of doping. As expected, Si has induced considerably more lattice distortions than C, and more than one order of magnitude l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 32 publications
(89 reference statements)
1
2
0
Order By: Relevance
“…Namely, with the in crease of the im planted fluence, the crys tal chan nels de te ri o rate caus ing more pro nounced en ergy loss that sub sequently chan neled ions ex pe ri ence, lead ing to shorter achieved ranges and crys tal dam age shift to wards the crys tal sur face. These re sults show good agree ment with pre vi ous stud ies [3,29].…”
Section: Ta Ble 1 Chan Nel Ing Ex Per I Ment Pa Ram E Ters -Ion Type ...supporting
confidence: 83%
“…Namely, with the in crease of the im planted fluence, the crys tal chan nels de te ri o rate caus ing more pro nounced en ergy loss that sub sequently chan neled ions ex pe ri ence, lead ing to shorter achieved ranges and crys tal dam age shift to wards the crys tal sur face. These re sults show good agree ment with pre vi ous stud ies [3,29].…”
Section: Ta Ble 1 Chan Nel Ing Ex Per I Ment Pa Ram E Ters -Ion Type ...supporting
confidence: 83%
“…Dekhili et al [ 145 ] reported new and complete mode assignments of Raman spectra in LiH 2 PO 4 and KLi(H 2 PO 4 ) 2 . Flessa et al [ 146 ] described Raman mapping of 4‐MeV C and Si channeling implantation of 6H–SiC. Gorelik and Pyatyshev [ 147 ] studied the Raman opalescence produced by a destabilizing soft mode near the phase transition in quartz monocrystals.…”
Section: Solid‐state Studiesmentioning
confidence: 99%
“…In fact, 6H-SiC crystals are a wide band gap material, meaning that the electronic devices made can work more reliably in harsh environments and can be widely used in aerospace, nuclear technology, and other high-temperature, high-radiation scenarios. In the study of phase transformation and amorphization of SiC, Aikaterini Flessa, M.Gloginjić, and others have done many experiments on the effect of irradiation cascade of 6H-SiC, and most of the researchers have studied the amorphization of 6H-SiC by high-energy, fast heavy ion injection using Raman spectroscopy and transmission electron microscopy methods [ 13 , 14 , 15 , 16 ]. K.Kamalakkannan et al, studied the induction behaviour and recrystallisation of 6H-SiC at different depths by low-energy ion injection [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%